Efeitos do carvão de coco babaçu e adubação organo-mineral na fertilidade de um argissolo cultivado com milho na periferia leste da Amazônia - Salgado, Gerbeli de Mattos (2011)
Charcoal when applied to the soil can provide benefits in chemical and physical attributes increasing crop production. The work had the objective to evaluate the effect of babassu charcoal associated with different sources of fertilizer on the development of corn and the fertility of an Argisol on the eastern outskirts of Amazon. The experimental design was in a 3x3 factorial scheme (3 doses of charcoal x 3 forms of fertilizer). Coal increased pH, decreased potential acidity of the soil, fixed and made P and K more available to the plant, with the absence of ash. The effects generated by coal occurred after just 45 days, disagreeing with the majority of the literature, which says that long periods are necessary for charcoal to take effect on the ground. It also positively affected the development of the plant, being observed greater accumulation of dry matter in the aerial part and greater root density. The coal when associated with a source of organic fertilizer, it promotes favorable conditions for good plant development. The application of charcoal as an agricultural practice may be viable since it brings benefits to the soil and plant development and can be a sustainable alternative to the tropics